Effects of addition of 2-fucosyllactose to infant formula on growth and specific pathways of utilization by Bifidobacterium in healthy term infants - Wallingford, John C.; Neve Myers, Pernille; Barber, Cynthia M. (Frontiers in Nutrition, 2022)
Oligosaccharides in human milk support health via intestinal microbiome. We studied effects of addition of 2-fucosyllactose (2′FL) to the infant formula on infant growth, occurrence of adverse events (AE), and infant microbiome, including expression of microbial genes that metabolize 2′FL. Our hypothesis was that while 2′FL would not affect growth, it would cause changes in microbiome metabolism. In a double-blinded randomized controlled study fashion, the infant formula ± 2′FL or human milk was fed to healthy term infants for 16 weeks. Fecal samples obtained at baseline and week 16 were analyzed for microbial populations, metagenomic species concept (MGS), and genetics of gut metabolic modules (GMMs). There were no effects of addition of 2′FL on growth or AEs. There were no significant differences by feeding group in MGS richness or Shannon diversity at baseline, but formula groups each had significantly greater richness (p < 0.05) and diversity (p < 0.05) after 16 weeks of feeding than the breastfed group. While two glycosyl hydrolase (GH) families (GH42 and GH112) were significantly increased, two other GH families (GH20 and GH2) were significantly decreased in the test formula group compared to the control formula group; although modest, addition of 2′FL resulted in changes in microbiome in the direction of breastfed infants, consistent with internal metabolism of HMOs by Bifidobacterium.